Phytochemical screening, antimicrobial activity and cytotoxicity of Nepalese medicinal plants Swertia chirayita and Dendrobium amoenum - Shrestha, Pritish; Bista, Manisha; Sharma, Prativa; Shrestha, Shristi; Lamichhane, Basanta; Adhikari, Sandeep; Pandey, Binayak Raj; Shrestha, Bhupal Govinda (Nepal Journal of Biotechnology, 2015)
Research on medicinal plants are important to Nepal because most of its rural population relies on it as mode of medicine. Medicinal plants namely Swertia chirayita and Dendrobium amoenum were collected from mid hills of Nepal. The present study was undertaken to find the antimicrobial activity, phytochemical presence and their cytotoxicity in different extraction medium. The percentage yield from the plants were highest in warm methanol extraction with 12.6%, followed by ethyl acetate and lowest was for cold methanol. Plant extract showed the presence of antioxidants like alkaloid, terpenoids, flavonoids, tannin, glycosides. The Brine Shrimp Bioassay of methanol and ethyl acetate extract showed cytotoxicity. Chiraito extract showed LC50 of 199 ppm for Dhunche sample, 128.82 ppm for Daman sample and 131.82 ppm of Illam sample. The antibacterial activity of methanol extract of Chiraito and Dendrobium amoenum showed significant bioactivity by inhibiting growth of microbial species selected for the test. The zone of inhibition shown by the extracts was comparable to the standard antibiotics. Similarly, methanol extract of Chiraito also showed significant antifungal activity with the zone of inhibition comparable to amphotericin. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 48-54